Characterization of Cr2O3 Nanoparticles Prepared Using Cauliflower Extract by Two Methods - Ali, Saja Q.; Aziz, Wisam J.; Sabry, Raad S. (Iraqi Journal of Science, 2021)
Chromium oxide nanoparticles were synthesized using cauliflower extract by two methods: simple chemical method and the sol-gel method. These technologies are new, environmentally friendly and cheap. Cauliflower contains plant materials and biomolecules (chromium, phenols, alkalis, vitamins, amino acids, quinones, etc. (that convert chromium chloride hexahydrate (CrCl3.6H2O) into chromium nanoparticles. The plant extracts also act as diluents, stabilizers and anti-caking agents. X-ray diffraction (XRD) analysis showed that the size of the crystals decreased from (36.1 to 57.8) nm using the simple chemical method to (13.31 to 20.68) nm of Cr2O3 using sol-gel. The scanning electron microscopy (SEM) showed that Cr2O3 NPs of the simple chemical method were Nano layers with (130.3) nm, while the Cr2O3 NPs of the sol-gel method were spherical or semispherical in shape with a particle size of (14.89 to 39.08) nm. The results obtained have no matches in the reported literature.. Ultraviolet-visible (UV-Vis) showed that the band gap energy of Cr2O3 NPs of the simple chemical method was 2.5 eV, while it was 3.4 eV for Cr2O3 NPs of the sol gel method . Cr2O3 NPs of high purity , small particle size, and large energy gap were obtained from the sol-gel method This means that the NPs from the sol gel method were better than those of the simple chemical method. The study revealed that the Chromium oxide nanoparticles synthesized using cauliflower extracts could be used as antibacterial agent for human pathogenic bacteria